2017
DOI: 10.5327/z1679443520170013
|View full text |Cite
|
Sign up to set email alerts
|

Exigências visuais e fadiga visual em médicos oftalmologistas

Abstract: ARTIGO ORIGINAL RESUMO | Contexto:As exigências visuais, designadamente da visão ao perto, são cada vez mais frequentes no mundo do trabalho, podendo causar fadiga visual ou astenopia. Os médicos oftalmologistas exercem atividades que exigem esforço visual, o que determina o interesse no seu estudo pela saúde ocupacional. Objetivos: Identificar a prevalência das queixas visuais e a sua relação com as exigências do trabalho nos médicos oftalmologistas em um hospital universitário de Lisboa. Métodos: Avaliou-se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 12 publications
(21 reference statements)
0
12
0
1
Order By: Relevance
“…However, in daily clinical practice, the cumulative time to perform vitrectomy is much longer than 2 h, which may increase the risk of abnormal ocular surface tissue. Previous studies have shown that the professional activities that ophthalmologists engage in for long time periods, including the application of computers, microscopes and slit lamps, can decrease blink frequency [ 11 ]. Yan et al showed that increasing amounts of high-intensity work performed by ophthalmologists lead to considerable alterations in tear dynamics, which can cause dry eye [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in daily clinical practice, the cumulative time to perform vitrectomy is much longer than 2 h, which may increase the risk of abnormal ocular surface tissue. Previous studies have shown that the professional activities that ophthalmologists engage in for long time periods, including the application of computers, microscopes and slit lamps, can decrease blink frequency [ 11 ]. Yan et al showed that increasing amounts of high-intensity work performed by ophthalmologists lead to considerable alterations in tear dynamics, which can cause dry eye [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ophthalmologists inevitably experience a decrease in the blink rate when using slit lamps or surgical microscopes, which may lead to changes in tear secretion [ 11 ]. The 3D head-up system differs significantly from the microscope eyepiece system in terms of intraocular illumination, operative field presentation, working distance, and surgical posture.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion criteria were as follows: All children were diagnosed with JPM based on the diagnostic standard of pseudomyopia adopted from the diagnostic standard of Theory and Methods of Optometry [ 28 ] ; age between 6 and 11 years; and Presence of blurred distance vision and susceptibility to visual fatigue. [ 29 ]…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion criteria were as follows: All children were diagnosed with JPM based on the diagnostic standard of pseudomyopia adopted from the diagnostic standard of Theory and Methods of Optometry [28] ; age between 6 and 11 years; and Presence of blurred distance vision and susceptibility to visual fatigue. [29] The exclusion criteria were as follows: Age <6 years or more than 11 years; Vision disorder secondary to other diseases; Accompanying other related managements; and Insufficient information on patient records.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…Esse processo é instintivamente exercido pelas pessoas para a manutenção da visão binocular, adquirindo assim uma importância clínica (DUKE-ELDER, 1997). No mundo contemporâneo, a presença quase onipresente dos dispositivos computacionais como smartphones, computadores, e-readers, entre outros, criam a necessidade do uso da visão para atividades diárias mais próxima aos olhos, necessitando assim da atenção visual para a execução de tais atividades (DZHODZHUA et al, 2017). Os autores ainda refletem que o microclima e a iluminação também podem influenciar o sistema visual.…”
Section: A Insuficência De Convergência: Conceitos Diagnóstico E Trat...unclassified